2010
DOI: 10.1128/iai.00921-09
|View full text |Cite
|
Sign up to set email alerts
|

Suppression ofPlasmodium cynomolgiin Rhesus Macaques by Coinfection withBabesia microti

Abstract: Both Plasmodium and Babesia species are intraerythrocytic protozoans that infect a wide range of hosts, including humans, and they elicit similar inflammatory responses and clinical manifestations that differ markedly in severity. We recently reported that a rhesus macaque that was chronically infected with Babesia microti was able to control infection with Plasmodium cynomolgi (a parasite of macaques with characteristics very similar to those of Plasmodium vivax) better than naïve monkeys. To confirm this and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Innate responses such as monocyte activation have been reported upon infection of monkeys with B. microti . Another study reported higher frequency of IL‐10–producing B cells (Bregs) and CD4+CD25+FoxP3+ T cells during the course of B. microti infection in mice .…”
Section: Discussionmentioning
confidence: 96%
“…Innate responses such as monocyte activation have been reported upon infection of monkeys with B. microti . Another study reported higher frequency of IL‐10–producing B cells (Bregs) and CD4+CD25+FoxP3+ T cells during the course of B. microti infection in mice .…”
Section: Discussionmentioning
confidence: 96%
“…The suppression of malaria infections in the course of ongoing babesiosis has been investigated in rhesus macaques ( Macaca mulatta ) in laboratory settings ( van Duivenvoorde et al., 2010 ), after it was found that a macaque infected with a B. microti -like parasite showed a suppressed Plasmodium cynomolgi infection ( Wel et al., 2008 ). Heterologous immunity between the two parasites has also been observed in mice ( Cox, 1978 , Zivkovic et al., 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous immunity between the two parasites has also been observed in mice ( Cox, 1978 , Zivkovic et al., 1984 ). It has been proposed that the cross-protection is most likely due to immune responses such as the activation of a distinct class of pro-inflammatory monocytes, release of pro-inflammatory cytokines, and increased C-reactive protein levels, which potentially play an important protective role in malaria infections ( Clark, 2001 , Ansar et al., 2006 , van Duivenvoorde et al., 2010 ). It has also been proposed that this heterologous immunity might be exploited for the development of malaria vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, Lobo et al reported that B. divergens and P. falciparum use the common receptors, glycophorins A and B, to invade the human erythrocyte [ 23 ]. Duivenvoorde LM et al reported that a rhesus macaque chronically infected with B. microti was able to control the infection with P. cynomolgi better than naïve monkeys [ 24 ]. The suppression of a Plasmodium infection after chronic exposure to B. microti warrants further investigation for a possible protective role of Babesia infection on Plasmodium .…”
Section: Reviewmentioning
confidence: 99%